Analyzing the Influence of Digital Learning Platforms on Student Engagement and Academic Performance - Baso Intang Sappaile; Eka Donna Fauziah Lasinggaru; Sabil Mokodenseho (Westscience Press, 2023)
This research study examines the impact of digital learning platforms and student engagement on academic achievement among secondary school students in Bandung. The study used a sample of 500 students from different schools representing different grade levels and socio-economic backgrounds. Data were collected through survey questionnaires and academic achievement measures obtained from school records. Descriptive, correlation, and regression analyses were conducted to analyze the data. The results showed a positive relationship between the use of digital learning platforms and student engagement. Students who used digital learning platforms more frequently showed higher levels of engagement. In addition, student engagement was found to positively affect academic achievement, suggesting that more engaged students tend to achieve better academic achievement. Regression analysis showed that digital learning platforms and student engagement significantly predicted academic achievement. After controlling for other factors, digital learning platforms accounted for 25% of the variance in academic achievement, while student engagement accounted for 15% of the variance. These findings highlight the combined effects of digital learning platforms and student engagement on academic achievement. The findings of this study have important implications for educational practice. Educators can utilize digital learning platforms to increase student engagement and improve academic outcomes. Policy makers should consider providing the necessary resources and infrastructure to ensure equitable access to digital learning platforms. Further research is recommended to explore strategies and best practices to optimize student engagement and maximize the potential of digital learning platforms.